Reformasi Dalam QS. Al-Kahfi: Telaah Konsep Al-Ishlāh Wa At-Taghyīr Sholāh Shulthān Serta Relevansinya Terhadap Fenomena Radikalisme di Indonesia - Mohammad Rindu Fajar Islamy; Didin Baharuddin (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Reform in QS. Al-Kahf: Examining the Concept of Al-Ishlāh Wa At-Taghyīr Sholāh Shulthān and Its Relevance to the Phenomenon of Radicalism in IndonesiaThis study aims to analyze the concept of Al-Ishlah wa At-Taghyir which was initiated by Sholah As-Shultan an international scholar and how its relevance to the phenomenon of radicalism in Indonesia. Studies of radicalism, terrorism and extremism have attracted the interest of scientists after the rampant acts of terror that occurred in Indonesia in the last two decades, such as the 2002 Bali bombings, and others. Reforms and improvements to deviations are fundamental things in human life, even the discourse is very much considered by Al-Quran Al-Karim. In QS Al-Kahf, there are several manhajs that are full of reform models to achieve community civilization to become more religious. The research was conducted through a qualitative approach. Through a literature study of Sholah Sulthan's primary work entitled Sūrah Al-Kahfi Manhajiyyāt Fī Al-Islāh Wa At-Tagyīr Dirāsāt Ta'shīliyyah Tathbīqiyyah, the secondary works were taken from other works. The results of the study show several conclusions including: 1) Reform and change are very much considered in the Qur'an, 2) in the QS. Al-Kahf forms of reform reform methods include several forms such as Manhajiyyatu At-Tadarruj min Al-Istid'āf ilā Al-Hiwār wa Minhā ilā At-Tamkīn, Manhajiyyatu Ba'tsu al-Amal Mahma Kāna al-Alam, and 3) Concepts of Al -Ishlah wa At-Taghyir has relevance to the phenomenon of radicalism in Indonesia, among its efforts is to trace the causal factors, then design preventive measures, collaborative efforts from various parties, and be patient with the process